Some properties of the p-brane model with the quadratic lagrangian - Miškinis, P. (Nonlinear Analysis: Modelling and Control, 1999)
Some general properties of the relativistic p-dimensional surface imbedded into D-dimensional space-time and its reduction to the simplest case of the quadratic Lagrangian are considered. The solutions of the equations of motion of such model for the p-brane with arbitrary topology and massless eigenstates, as well as with critical dimension after quantization are presented. Some generalizations for the supermembrane are discussed.